Audit procedures applied for auditing staff cost in small And medium construction entities at kpmg vietnam - Ta, Ngoc Anh (2020)
The study investigated and sought to establish the audit process and audit procedures that applied for auditing staff cost related accounts at KPMG for construction firms as well as the strengths and limitations of these procedures. The research was conducted using qualitative approach using Survey, Interview and Case study as Research Designs. The study found that the audit risk of payroll cycle in construction firms is relative low and KPMG staff quite satisfied with the guideline of company about the procedures. This study also gives advices for further research in audit profession about the methodology and topic of research.